Adam's dust and Adam's glory in the Hodayot and the Letters of Paul rethinking anthropogony and theology - Meyer, Nicholas A. 1978- (Supplements to Novum Testamentum, 2016)
"In Adam's Dust and Adam's Glory, Nicholas A. Meyer challenges the scholarly reconstruction of a traditional theological framework of creation, fall, and restoration in order to comprehend the pessimistic anthropologies of the Hodayot and the letters of Paul. Meyer argues that too little notice has been paid to the fact that this literature problematizes ordinary humanity by way of original humanity--its sexuality, its earthly physicality, its spiritual-moral frailty--and that these texts look not for the restoration of human nature as determined in creation, but rather for its transformation. Setting aside the traditional threefold framework, the author offers an innovative and comprehensive reading of the use of traditions of anthropogony, including the glory of Adam and the image of God, in this literature"--